Exploring entrepreneurship and economics - Greene, Cynthia L. (Thomson / South-Western, 2007)
EXPLORING ENTREPRENEURSHIP, a student text with data CD, provides a pleasing visual presentation and uses relevant examples to make the material engaging for students. Designed for middle/junior high school, students learn concepts and processes associated with successful entrepreneurial performance, which gives them a realistic view of entrepreneurship. A consistent use of easy-to-find features in each chapter will help students relate to prior knowledge, their experiences, and other core subjects. Based on real-life experiences of teenage entrepreneurs, the text teaches critical thinking skills by using relevant activities. Students who use EXPLORING ENTREPRENEURSHIP develop career decision-making skills that they can use for a lifetime, practice problem solving, integrate the study of personal finance topics as appropriate, and become more aware of the role of entrepreneurs and free enterprise in the workplace of the 21st century. As a culminating activity, students work in teams to develop a proposal to start a new business, a self-analysis (including the willingness to take risks), an analysis of the business situation, and a description of the way the business will operate. A general explanation of the financing of the business throughout the first three years of operation is also taught. Students are encouraged to apply entrepreneurial skills to a single sales/service activity to be run as a real business venture. The sales/service activity may focus on any subject of interest to the team and should involve all the members of the team.